2012
DOI: 10.1007/s10719-012-9369-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-arabinofuranoside glycolipids, studies of their binding to surfactant protein-A and effect on sliding motilities of M. smegmatis

Abstract: Surfactant protein A (SP-A), which is a lung innate immune system component, is known to bind glycolipids present at the cell surface of a mycobacterial pathogen. Lipoarabinomannan (LAM), a component of mycobacterial thick, waxy cell wall, is one of the glycolipid ligands for SP-A. In order to assess binding of synthetic glycolipids with SP-A and the glycosidic linkage preferences for the interaction, β-arabinofuranoside trisaccharide glycolipids constituted with β-(1→2), β-(1→3) and β-(1→2), β-(1→5) linkages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…The glycolipids are composed of lipidic and mannan portions, which qualitatively follow the pattern of components present in mycobacterial cell wall bound lipomannans. Our earlier studies on a series of synthetic oligoarabinan and oligoarabinomannan glycolipids demonstrated a reduction in mycobacterial growth upon treatment with these glycolipids . A pertinent query in these studies is the role of glycolipids composed of individual sugar moieties, as opposed to mixed oligoarabinomannan glycolipids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The glycolipids are composed of lipidic and mannan portions, which qualitatively follow the pattern of components present in mycobacterial cell wall bound lipomannans. Our earlier studies on a series of synthetic oligoarabinan and oligoarabinomannan glycolipids demonstrated a reduction in mycobacterial growth upon treatment with these glycolipids . A pertinent query in these studies is the role of glycolipids composed of individual sugar moieties, as opposed to mixed oligoarabinomannan glycolipids.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas oligoarabinomannan glycolipids show potent mycobacterial inhibitory activities in growth and biofilm phases, studies on oligoarabinan‐containing glycolipids show weaker inhibitory effects on growth phases and biofilm formation of M . smegmatis . We also recently identified that synthetic glycolipids supplemented the inhibition activities of the drug isoniazid on biofilm‐grown mycobacterium; thus suggesting the role of glycolipids on the drug involved in the inhibition of cell wall biosynthesis .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Biofilm quantification was carried out in three biological replicates. A parallel experiment was carried out in which OD 600 of all the strains was monitored to measure the cell culture density (Naresh et al., ; Syal, ).…”
Section: Methodsmentioning
confidence: 99%
“…As fouling-resistant SAMs: Synthesis, monolayer properties, and antifouling behavior (Fyrner et al, 2011) Sucrose monolaurate TOF Synthesis from sucrose and vinyl laurate by action of alkaline protease from Bacillus licheniformis (Laurino et al, 2011) 3-Thioglycosylated 5,6-diacetoxyindole derivatives TOF Thioglycosylation using a selenium-based dynamic-mixture method (Adinolfi et al, 2012) Glycolipids Arabinofuranoside-containing glycolipids TOF Synthesis and interaction with surfactant protein A (Naresh et al, 2011) Arabinofuranoside-containing glycolipids TOF Synthesis and binding to surfactant protein A and effect on sliding motilities of M. smegmatis (Naresh et al, 2012) Cholesteryl-6-Otetradecanoyl--Dglucopyranoside MALDI Chemoenzymatic synthesis 4…”
Section: Tof (Dhb)mentioning
confidence: 99%